Maternal perceptions and experiences of breastfeeding support in Baby-Friendly hospitals: An integrative review - Jaana Lojander; Heli Mäkelä; Hannakaisa Niela-Vilén (Elsevier, 2022)
Background: The Baby-Friendly Hospital Initiative aims to improve breastfeeding by implementing the Ten Steps to Successful Breastfeeding (Ten Steps) into routine breastfeeding support in birth hospitals. Maternal perspective to breastfeeding support is important to consider as mothers and their infants are in the center of that support. Objectives: To review and synthesize the existing literature on maternal perceptions and experiences of breastfeeding support in Baby-Friendly hospitals. A sub-aim was to describe differences in breastfeeding support between Baby-Friendly hospitals and non-Baby-Friendly hospitals from maternal perspective. Data sources and review methods: An integrative literature review. A systematic literature search was conducted in October 2021 in five databases: PubMed, CINAHL, Cochrane, Scopus, Web of Science. Original peer-reviewed studies published in English exploring maternal viewpoints on breastfeeding support in Baby-Friendly hospitals were included. Two reviewers independently screened the titles (n=914), abstracts (n=226), and full texts (n=47). The review comprised of seventeen studies and includes both quantitative studies (n=14) and qualitative studies (n=3). Inductive content analysis and descriptive synthesis were conducted. Results: Most studies (n=14) measured hospitals' compliance with the Ten Steps practices from maternal perspective. Mothers were provided with breastfeeding information and encouragement, however, a qualitative finding indicated that information focused on positive aspects of breastfeeding. Early skin-to-skin contact between the mother and infant was well facilitated although often not lasting more than 30 min. Breastfeeding was facilitated by practical support but according to findings of two qualitative studies, support was not always adequate to address mothers' problems with breastfeeding. Most mothers were exclusively breastfeeding during the hospital stay and no supplemental milk was offered to infant. Mothers were roomed-in together with their infant and were mostly encouraged to breastfeed on demand. Differences between Baby-Friendly hospitals and non-Baby-Friendly hospitals were observed particularly for steps 6 and 9: supplementary feeding and pacifier use were less common in Baby-Friendly hospitals. Conclusions: From the maternal perspective, breastfeeding support in the Baby-Friendly hospitals was mainly but not completely in adherence with the Ten Steps practices. Low compliance with some of the Ten Steps indicates a need for a more frequent assessment of the breastfeeding support practices and consideration of strategies facilitating a more sustainable implementation of the initiative. Regardless of some shortcomings with the breastfeeding support, mothers were mainly satisfied with the support in the hospital. Mothers in the Baby-Friendly hospitals perceived that breastfeeding support was more adherent to the Ten Steps compared to mothers in non-Baby-Friendly hospitals.